Role-Based Access Control (RBAC) in Modern Cloud Security Governance: An In-depth Analysis - Arun Kumar Akuthota (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the evolving role of Role-Based Access Control (RBAC) in modern cloud security governance, with particular emphasis on its implementation within SAP Business Technology Platform environments. The article investigates how RBAC has transformed from a traditional access control mechanism into an AI-enhanced security framework capable of addressing contemporary cloud security challenges. Through examination of real-world implementations, the article demonstrates RBAC’s effectiveness in reducing security incidents, streamlining administrative processes, and ensuring regulatory compliance. The article explores the integration of artificial intelligence and machine learning capabilities, which have significantly enhanced RBAC’s ability to detect and prevent security threats while optimizing role management. Furthermore, the article evaluates the impact of RBAC on organizational efficiency, risk management, and scalability, providing insights into best practices for implementation and future trends in access control systems. Special attention is given to the convergence of RBAC with emerging technologies such as blockchain and zero trust architecture, offering a forward-looking perspective on the evolution of cloud security governance.